Drug-Drug Interactions Between HIV Antivirals and Concomitant Drugs in HIV Patients: What We Know and What We Need to Know - Emanuela De Bellis; Danilo Donnarumma; Adele Zarrella; Salvatore Maria Mazzeo; Annarita Pagano; Valentina Manzo; Ines Mazza; Francesco Sabbatino; Graziamaria Corbi; Pasquale Pagliano; Amelia Filippelli; Valeria Conti (Pharmaceutics)
Highly active antiretroviral therapy has led to a significant increase in the life expectancy of people living with HIV. The trade-off is that HIV-infected patients often suffer from comorbidities that require additional treatment, increasing the risk of Drug-Drug Interactions (DDIs), the clinical relevance of which has often not been determined during registration trials of the drugs involved. Therefore, it is important to identify potential clinically relevant DDIs in order to establish the most appropriate therapeutic approaches. This review aims to summarize and analyze data from studies published over the last two decades on DDI-related adverse clinical outcomes involving anti-HIV drugs and those used to treat comorbidities. Several studies have examined the pharmacokinetics and tolerability of different drug combinations. Protease inhibitors, followed by nonnucleoside reverse transcriptase inhibitors and integrase inhibitors have been recognized as the main players in DDIs with antivirals used to control co-infection, such as Hepatitis C virus, or with drugs commonly used to treat HIV comorbidities, such as lipid-lowering agents, proton pump inhibitors and anticancer drugs. However, the studies do not seem to be consistent with regard to sample size and follow-up, the drugs involved, or the results obtained. It should be noted that most of the available studies were conducted in healthy volunteers without being replicated in patients. This hampered the assessment of the clinical burden of DDIs and, consequently, the optimal pharmacological management of people living with HIV.